Perlindungan Hukum Bagi Pasien Selaku Konsumen terhadap Tindakan Malpraktik di Bidang Kesehatan - Sutono Widjaja (JURNAL RECHTENS, 2020)
Malpractice cases are a crime that is very common in Indonesia. Malpractice is basically the actions of professionals who contravene SOPs, codes of ethics, and applicable laws, whether intentional or as a result of negligence resulting in loss or death to others. On the other hand, in the implementation of health services, medical personnel, namely doctors and nurses do not rule out the possibility of an error or negligence. Errors or negligence by doctors in carrying out their professional duties can be fatal both to the body and soul of the patient (in medical/legal terms this incident is called malpractice) and this is of course very detrimental to the patient as a victim of malpractice. As a victim of malpractice that is harmed , of course the patient will demand what is his right. Patients who are victims of malpractice will demand compensation or ask for accountability from the doctor concerned. These demands can be in the form of civil claims, namely compensation, criminal charges, namely imprisonment for perpetrators of malpractice